First Case of Allochronic Onset of Two Primary Dermatofibrosarcoma Protuberans Lesions Proved by COL1A1-PDGFB Fusion Gene Analysis - Ayano Ikeda; Masanori Hisaoka; Hiroyuki Goto; Yuichi Yoshida; Osamu Yamamoto (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)